Engaging underrepresented groups in community physical activity initiatives: a qualitative study of parkrun in the UK - Helen Quirk (BMC, 2024)
Abstract Background Underrepresented groups, including racial/ethnic minority groups and individuals with low socioeconomic status face complex barriers to engaging in community-based health initiatives. This research uses parkrun, an outdoor, mass-participation, weekly physical activity and volunteering initiative, to explore the engagement strategies ('outreach activities') that have been used to promote the inclusivity and diversity of parkrun events. Methods Ten adult parkrun Ambassadors who fulfilled volunteer roles that involved promoting parkrun to underrepresented groups in the UK were interviewed. Interviews took place via telephone or video call in April-July 2021. Interview transcripts were analysed thematically. Results Engagement strategies implemented by Ambassadors varied from opportunistic promotion within communities to strategic negotiations at higher decision-making levels. Approaches were characterised by a community-centred focus that ensured community networks and assets were utilised. Stories were considered valuable indicators of successful outreach. A common challenge to outreach for Ambassadors was limited personal and organisational capacity that impeded the widescale scope, reach and scalability of parkrun's engagement attempts. Conclusions Parkrun Ambassadors have used a wide range of outreach activities at different levels of influence. A number of challenges to doing sustainable and effective outreach have been highlighted that need to be addressed. Working with and alongside communities where community-based health initiatives events take place to understand how to address inclusivity issues could contribute to greater participation by underrepresented groups.